ANALISIS PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA LQ45) - Delvi Dwinky Zutami; Harsi Romli; Luis Marnisah (Program Magister Manajemen Indo Global Mandiri University, 2021)
In this globalization era, every company both small and large companies compete with each other with the aim to maintain and advance the life of the company. In this study the profitability ratio is measured by return on equity (ROE). Return on equity (ROE) is a ratio that shows the company's ability to generate net income for return on shareholders' equity. In this study, the sample that will be used is consumer goods companies listed in LQ45 for the period of 2012 to 2016. LQ45 is chosen based on the availability of complete financial statement data, companies listed in LQ45 have been categorized as having a level of liquidats, profitability and company value from year after year is in good condition compared to companies that are not listed in LQ45, so it is expected that testing of the ratios can be done thoroughly in accordance with the objectives of this study. Food and Beverage Companies in LQ45 which the authors make as a sample of this research are: PT. Unilever Indonesia, Tbk (UNVR), PT. Indofood Sukses Makmur, Tbk (INDF), PT. Indofood CBP Sukses Makmur, Tbk (ICBP). The test results prove that: partially, the Capital Structure (DER) of the Company has a positive effect on firm value, company growth has no effect on firm value, profitability has a negative effect on Company Value (PBV) and simultaneously capital structure, company growth, and profitability have an effect on the value of the company. To increase its growth, food and beverage companies listed on the IDX LQ45 must pay attention to capital structure by utilizing productive use of debt to increase company value.